Impact of Buffer Layer on Electrical Properties of Bow-Tie Microwave Diodes on the Base of MBE-Grown Modulation-Doped Semiconductor Structure - Algirdas Sužiedėlis; Steponas Ašmontas; Jonas Gradauskas; Aurimas Čerškus; Aldis Šilėnas; Andžej Lučun (Crystals)
Bow-tie diodes on the base of modulation-doped semiconductor structures are often used to detect radiation in GHz to THz frequency range. The operation of the bow-tie microwave diodes is based on carrier heating phenomena in an epitaxial semiconductor structure with broken geometrical symmetry. However, the electrical properties of bow-tie diodes are highly dependent on the purity of the grown epitaxial layer—specifically, the minimal number of defects—and the quality of the ohmic contacts. The quality of MBE-grown semiconductor structure depends on the presence of a buffer layer between a semiconductor substrate and an epitaxial layer. In this paper, we present an investigation of the electrical and optical properties of planar bow-tie microwave diodes fabricated using modulation-doped semiconductor structures grown via the MBE technique, incorporating either a GaAs buffer layer or a GaAs–AlGaAs super-lattice buffer between the semi-insulating substrate and the active epitaxial layer. These properties include voltage sensitivity, electrical resistance, I–V characteristic asymmetry, nonlinearity coefficient, and photoluminescence. The investigation revealed that the buffer layer, as well as the illumination with visible light, strongly influences the properties of the bow-tie diodes.